Study on the volute chamber shape of swirling shaft adopted in water diversion project. Issue 4 (February 2019) - Li, Yang; Zhang, Rongbin; Yang, Lei; Han, Pengpeng; Wang, Yisen; Xu, Chang
Abstract: As an environment-friendly internal energy dissipation technology, the swirling shaft energy dissipation has been more and more applied. In this paper, the influence of the shape of the volute chamber on the flow pattern and energy dissipation rate is studied by the CFD numerical simulation method combined with the physical model test method. The results show that with the increasing of the diameter of the volute chamber, the diameter of the cavity in the volute chamber increases correspondingly, which effectively alleviates the backwater phenomenon on the upstream channel section of the shaft. Increasing the width of the inlet of the volute chamber can promote the flow pattern of the upstream channel section from the pressure flow to the non-pressure flow. The setting of the arc wedge rectification flip bucket can improve the inlet and inner flow pattern of the volute chamber.